Digital Holographic Microscopy as Identifier of Ultrafine Particles Emitted during Fused Deposition Modelling - Daniel Alberto García-Espinosa; Miguel León-Rodríguez; Pedro Yañez-Contreras; Israel Miguel-Andrés; José Alfredo Padilla-Medina; Alejandra Cruz-Bernal; Patricia Ibarra-Torres (Applied Sciences, 2021)
Additive manufacturing has acquired a global industrial panorama for being an alternative to redirect the industry towards sustainability. However, previous studies have indicated that fused deposition modelling (FDM) techniques are potential sources of particles that are harmful to health. For this reason, this work is focused on exploring the behaviour and distribution of FDM resultant nanoparticles from the most commonly used printable materials through alternative methods as digital holographic microscopy (DHM). In this paper, we present the feasibility of using DHM to determine the presence of nanoparticles in the FDM process. Experimental results validate this technology’s precision and provide extensive knowledge about the implications of the FDM on health. The measure of the thin films deposited in glass substrates was between a minimum of 9 nm to a maximum of 200 nm, in agreement with the previous studies.